APLIKASI MUTAN BERFLUORESENS UNTUK MEMPELAJARI KETAHANAN HIDUP, KOLONISASI DAN PENETRASI ISOLAT Cronobacter sakazakii SELAMA PENGERINGAN JAGUNG [Use of GFP Mutant to Study the Survival, Colonization and Penetration of Cronobacter sakazakii Isolates Duri - Siti Nurjanah; Maggy T. Suhartono; Ratih Dewanti- Hariyadi; Sri Estuningsih (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2013)
Cronobacter sakazakii is a Gram-negative emerging pathogen regarded as causative agent of meningitis and necrotizing enterocolitis in certain groups of infants. In the previous research, thirty-two local isolates of C. sakazakii were obtained from various dried food products such as from corn starch, suggesting that they are able to survive drying. Some of the isolates were toxic. Green Fluorescent Protein (GFP) have been inserted to C. sakazakii and used as a marker for selective enumeration due to the ability of this protein to fluoresce under UV and to tolerate in ampicillin containing media. The objective of this study was to evaluate the survival, colonization and penetration of two isolates of C. sakazakii from dried food product during maize drying. The maize was challenged with mutants at a concentration of 105-106 CFU/g before drying. Maize drying was performed at temperature of 40ºC, 45ºC and 50ºC for 4, 6 and 8 days until the moisture content reached 14%. The totals of resistant drying mutants were counted every day onto ampicillin containing media by observing under UV light. The survival rate of C. sakazakii during drying was determined by the slope of linier regression from C. sakazakii survival curve. Isolates of FWHd16, the toxic strain of C. sakazakii, were more resistant to heat treatments in comparison to isolates of YRt2a, or the non toxic strain of C. sakazakii. Following fluorescence and scanning electron microscope observation, it is concluded that both isolates were colonizing on maize surface. These mutants were able to penetrate to the inner side of the grain by entering injured surface or pores at the tip cap of maize.